An overview of the evidence to guide decision-making in acupuncture therapies for early recovery after acute ischemic stroke - Wang, Liuding; Chi, Xiansu; Lyu, Jian; Xu, Zhenmin; Fu, Guojing; Liu, Yue; Liu, Shaojiao; Qiu, Wenran; Liu, Hongxi; Liang, Xiao; Zhang, Yunling (Frontiers in Neurology, 2022)
Background Acupuncture is a proven technique of traditional Chinese medicine (TCM) for ischemic stroke. The purpose of this overview was to summarize and evaluate the evidence from current systematic reviews (SRs) of acupuncture for early recovery after acute ischemic stroke (AIS). Methods We performed a comprehensive search for SRs of acupuncture for AIS in seven electronic databases up to May 23, 2022. Two reviewers independently selected SRs, extracted data, evaluated the methodological quality using the Assessment of Multiple Systematic Reviews 2 (AMSTAR 2), and rated evidence certainty using the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE). Results Seven SRs were included. The overall methodological quality of SRs was critically low. As for GRADE, 3 outcomes had moderate-quality evidence, 14 had low-quality evidence, and 12 had very low-quality evidence. Moderate-quality evidence demonstrated that initiating acupuncture therapies within 30 days of AIS onset significantly improves neurological function and the total effective rate of patients. Low-quality evidence showed that for patients within 2 weeks of AIS onset Xingnao Kaiqiao acupuncture (XNKQ Ac) could reduce disability rate and might reduce mortality. Regarding the safety of acupuncture therapies, low-quality evidence showed that there was no difference in the incidence of adverse reactions between the 2 groups, and very-low quality evidence showed that acupuncture did not promote hemorrhagic conversion. Conclusions In the acute and early recovery phases after AIS onset, acupuncture is a promising therapeutic strategy to improve the curative effect of current treatments, especially in the recovery of neurological function. Patients in the acute phase might receive XNKQ Ac, and patients in the early recovery phase might receive EA1, CA, or SA. However, considering the current certainty of evidence, a solid recommendation warrants further exploration. Systematic review registration:https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42022335426.